Resistance of Female Characters Against Patriarchal Cultural Values in Dian Purnomo’s Novel Perempuan yang Menunggu di Lorong Menuju Laut - Nadia Aprisilia; Yessi Fitriani; Muhammad Ali (Journal of Social Work and Science Education, 2027)
This article examines the resistance of female characters against patriarchal cultural values in Dian Purnomo’s novel Perempuan yang Menunggu di Lorong Menuju Laut through feminist literary criticism. The study applies a qualitative descriptive method by using the novel as the primary data source. Data were collected through close reading and note-taking, then classified according to patriarchal cultural values and three forms of female resistance: verbal, action, and psychological resistance. The results show that patriarchal culture in the novel is represented through male domination, restriction of women’s freedom, gender stereotypes, domestic expectations, and social pressure that limits women’s roles in family and society. Female characters respond to these pressures through critical utterances, slogans, speeches, demonstrations, sea actions, collective legal strategies, emotional endurance, and self-awareness. The discussion indicates that resistance in the novel is a continuous process: psychological awareness produces courage to speak, verbal resistance builds collective consciousness, and action resistance transforms awareness into social struggle. The novel therefore functions not only as a representation of women’s suffering under patriarchal culture, but also as a literary space that affirms women as active subjects, agents of change, and bearers of cultural criticism.